Proceedings of the 2010 Winter Simulation Conference 2010
DOI: 10.1109/wsc.2010.5678946
|View full text |Cite
|
Sign up to set email alerts
|

Generating dispatching rules for semiconductor manufacturing to minimize weighted tardiness

Abstract: Dispatching rules play an important role especially in semiconductor manufacturing scheduling, because these fabrication facilities are characterized by high complexity and dynamics. The process of developing and adapting dispatching rules is currently a tedious, largely manual task. Coupling Genetic Programming (GP), a global optimization meta-heuristic from the family of Evolutionary Algorithms, with a stochastic discrete event simulation of a complex manufacturing system we are able to automatically generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 25 publications
0
16
0
1
Order By: Relevance
“…For example, Tay and Ho [135] applied GP to evolve dispatching [73] rules for flexible job shop scheduling and use the least waiting time assignment [49] to find a suitable machine to process an operation. Similarly, Pickardt et al [117] evolved dispatching rules for semiconductor manufacturing and used two existing heuristics, i.e. minimum batch size (MBS) and larger batches first (LBF), to control batch formulation.…”
Section: Component(s) To Be Evolvedmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Tay and Ho [135] applied GP to evolve dispatching [73] rules for flexible job shop scheduling and use the least waiting time assignment [49] to find a suitable machine to process an operation. Similarly, Pickardt et al [117] evolved dispatching rules for semiconductor manufacturing and used two existing heuristics, i.e. minimum batch size (MBS) and larger batches first (LBF), to control batch formulation.…”
Section: Component(s) To Be Evolvedmentioning
confidence: 99%
“…Nie et al [100] Pickardt et al [117] Baykasoglu et al [11] Abednego and Hendratmo [1] Nguyen et al [85] Nie et al [101] Nie et al [102] Vazquez-Rodriguez and Ochoa [136] Attribute analysis Interpretability Generalisability Jakobovi and Marasovi [58] Nguyen et al [86] Nguyen et al [87] Nie et al [103] Han et al [41] Nguyen et al [88] Nguyen et al [89] Nguyen et al [90] Nguyen et al [91] Nie et al [104] Park et al [110] Park et al [111] Pickardt et al [118] Qin et al [122] Nie et al [105] Hildebrandt and Branke [45] Hildebrandt et al [47] Hunt et al [53] Hunt et al [54] Nguyen et al [93] Nguyen et al [92] Nguyen et al [94] Nguyen et al [95] Nguyen et al [96] Park et al [112] Alsina et al [3] Belisrio and Pierreval [15] Sim and Hart [130] Branke et al [18] …”
mentioning
confidence: 99%
“…These are usually metaheuristics such as Evolutionary Algorithms (EAs) that search over a space of heuristics. Various papers have shown that in particular Genetic Programming (GP) can be successfully used to generate dispatching rules for scheduling scenarios that significantly out-perform manually developed benchmark rules , Pickardt et al 2010, Pickardt et al 2013, Geiger et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Genetic Programming (GP) gained popularity as an effective optimization technique [1], and its capabilities of automatically uncovering hidden relationships in datasets and producing rules to control complex systems haves been proved in several real-world applications [2] [3].…”
Section: Introductionmentioning
confidence: 99%